PERANAN SYEKH WALID THAIB SALEH INDRAGIRI DALAM MENYEBARKAN AGAMA ISLAM DI KABUPATEN INDRAGIRI HILIR - Meriani, Meriani; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The word "Islam" is derived from the word aslama means surrender, not only does Islam mean peace, salvation, submission to Allah but also means do the virtues of those who recognize the religion of Islam is called muslim. The birth of the Islamic religion brought by the Prophet SAW in the 7th century AD, creates an extraordinary driving force that has ever been experienced by mankind. One of them is Syekh Walid Thaib Saleh Indargiri who spread the Islamic religion in Indragiri especially in Gaung Anak Serka precisely in the village of Teluk Sungka. The purpose of this research is (1) To know the history of Syekh Walid Thaib Saleh Indragiri (2) To know the role of Syekh Walid Thaib Saleh Indragiri in spreading Islam in Indragiri Hilir district (3) To know what barriers felt by Sheikh Walid Thaib Saleh Indragiri Hilir developing Islam in Indragiri Hilir Regency. In this study using qualitative research methods. Qualitative is a method that does not use numbers in data collection and in providing interpretation of the results. The result of this study is Sheikh Walid Thaib Saleh Indragiri is a scholar, in mengehbarkan Islam religion in the village of Teluk Sungka in 1940 M. the role of Sheikh Walid Thaib Saleh Indragiri teachings for the people of Teluk Sungka village can be seen from the efforts made in the field of education and da'wah, has brought great changes to the Indragiri community, especially in the village of Teluk Sungka.Keywords: Position, Spread of Islam